Changes for Felicity: A Winter Story - Tripp, Valerie (Pleasant Company Publications Incorporated, 1992)
The outbreak of the Revolutionary War in 1775 brings drastic changes to Felicity's life in Williamsburg.
Keywords: Friendship; Juvenile Fiction; Social Issues